Fabrication and high-temperature tribological behaviors of Al2O3/Cr2O3 composites with three-dimensional continuous structure. (February 2023) - Zhang, Xiaoyu; Song, Junjie; You, Xin; Sun, Qiuan; Su, Yunfeng; Huang, Xiaopeng; Fan, Hengzhong; Hu, Litian; Zhang, Yongsheng
Graphical abstract: Highlights: We evaluate the friction and wear properties of Al2 O3 /Cr2 O3 composites at 800 °C and 1000 °C. The properties were improved significantly by using 3D continuous structure design. The 3D continuous structure promotes the formation of friction films and transfer films. The optimized structure lead to the enhanced load-carrying capacity and reduced failure. A set of principles to design Al2 O3 /Cr2 O3 composites with high properties were formulated. Abstract: A new strategy for improving high-temperature compressive strength and tribological properties of Al2 O3 /Cr2 O3 composites was proposed in this study. The three-dimensional (3D) continuous Al2 O3 ceramic matrix containing Cr2 O3 particles was fabricated, and the influencing mechanisms of compositions and structures on the anti-wear and friction-reducing performance of composites at high temperature were revealed. Results show that the enrichment degree of Cr2 O3 in the composites can be significantly improved based on the 3D continuous structure design compared with Al2 O3 /Cr2 O3 composite containing uniform compositions. Under friction conditions, the Cr2 O3 phase with large enrichment degree can preferentially contact with the micro-asperities on the friction pair surface under the action of grain refinement at high temperature, so that the softened Cr2 O3 is easy to be sheared and dragged to the worn surfaces of the friction couples to form the friction film and transfer film. Meanwhile, under the favorable effect of the high load-carrying capacity of continuous Al2 O3 matrix, Al2 O3 /Cr2 O3 composites show excellent tribological properties at high temperature. The friction coefficient and wear rate of Al2 O3 /Cr2 O3 composites with 3D continuous structure sliding against Al2 O3 pin can be reduced to 0.35 and 2.2 × 10 -6 mm 3 ·N -1 m −1 at 800 °C, and it still presents excellent friction-reducing and anti-wear properties at 1000 °C.